The two-component system BvrR/BvrS essential for Brucella abortus virulence regulates the expression of outer membrane proteins with counterparts in members of the Rhizobiaceae - Guzmán-Verri, C. (National Academy of Sciences, 2002)
The Brucella BvrR/BvrS two-component regulatory system is homologous to the ChvI/ChvG systems of Sinorhizobium meliloti and Agrobacterium tumefaciens necessary for endosymbiosis and pathogenicity in plants. BvrR/BvrS controls cell invasion and intracellular survival. Probing the surface of bvrR and bvrS transposon mutants with monoclonal antibodies showed all described major outer membrane proteins (Omps) but Omp25, a protein known to be involved in Brucella virulence. Absence of Omp25 expression was confirmed by two-dimensional electrophoresis of envelope fractions and by gene reporter studies. The electrophoretic analysis also revealed reduction or absence in the mutants of a second set of protein spots that by matrix-assisted laser desorption ionization MS and peptide mass mapping were identified as a non-previously described Omp (Omp3b). Because bvrR and bvrS mutants are also altered in cell-surface hydrophobicity, permeability, and sensitivity to surface-targeted bactericidal peptides, it is proposed that BvrR/BvrS controls cell envelope changes necessary to transit between extracellular and intracellular environments. A genomic search revealed that Omp25 (Omp3a) and Omp3b belong to a family of Omps of plant and animal cell-associated α-Proteobacteria, which includes Rhizobium leguminosarum RopB and A. tumefaciens AopB. Previous work has shown that RopB is not expressed in bacteroids, that AopB is involved in tumorigenesis, and that dysfunction of A. tumefaciens ChvI/ChvG alters surface properties. It is thus proposed that the BvrR/BvrS and Omp3 homologues of the cell-associated α-Proteobacteria play a role in bacterial surface control and host cell interactions.